PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN, DAN KOMUNIKASI TERHADAP DISIPLIN KERJA PADA BADAN PENDAPATAN DAERAH BANYUWANGI - Nilawati, Wardha; Dewati, Ni Kadek Wira; Wicaksono, Bambang (Widya Amerta, 2023)
The problem that is most often faced by an organization to achieve its goals is how to improve the work discipline of its employees properly.  If work discipline is not applied and not adhered to, it will be difficult for an organization to achieve optimal results.  So that in improving work discipline an organization requires factors that can affect work discipline, namely organizational culture, leadership style, and communication.This study aims to determine the influence of organizational culture, leadership style, and communication on work discipline.  This research is a quantitative research.  The subjects of this study were employees of the Banyuwangi Regional Revenue Agency as many as 33 respondents.  Data processing in this study using SPSS version 25 for windows.  With the first result, there is a positive and significant influence between the variables of Organizational Culture on Work Discipline.  Second, there is a positive and significant influence between the variables of Leadership Style on Work Discipline.  And third, there is no significant effect between the variables of Communication on Work Discipline.